Vocational recovery in mental illness - the gap between policy and person-centredness - Netto, Julie Ann (Curtin University, 2013)
Vocation has been described as a calling and a means of fulfilment; and personal recovery as the process of living life as well as possible. Vocational recovery can be envisaged as a person with mental illness regaining or establishing valued roles associated with vocation as it is broadly defined. This thesis explores how people with mental illness establish and achieve their vocational recovery goals within the context of complex and ever-changing policy and service settings.